The drillmaster of Valley Forge : the Baron de Steuben and the making of the American Army - Lockhart, Paul Douglas, 1963- (New York : Harper, 2008)
A biography of the Revolutionary War general, Baron von Steuben--Friedrich Wilhelm Ludolf Gerhard Augustin von Steuben--that focuses on his military career, and describes his efforts to create West Point and his contributions to the "Blue Book," which detailed army regulations.
The finest school of warfare in the world -- Courtier and supplicant -- This illustrious stranger -- A man profound in the science of war -- On the parade-ground at Valley Forge -- Jealousies and hindrances -- Trial by combat -- The blue book -- The true meaning of discipline -- Tormenting the governor -- From Virginia to Fraunces Tavern -- An old soldier in peacetime.
Includes bibliographical references (p. [303]-319) and index.
Keywords: Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794 -- Military leadership; United States. -- Continental Army -- Drill and tactics; Military art and science -- United States -- History -- 18th century; Valley Forge (Pa.) -- History, Military -- 18th century; United States -- History -- Revolution, 1775-1783 -- Campaigns; Generals -- United States -- Biography; United States. -- Continental Army -- Biography; Prussians -- United States -- Biography; United States -- History -- Revolution, 1775-1783 -- Participation, Prussian; Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794.; United States. -- Continental Army; Armed Forces -- Drill and tactics; Generals; Military art and science; Military leadership; Prussians; Pennsylvania -- Valley Forge; United States; 1700 - 1799; Biography; History; Military history